IMPROVING THE STUDENTS’ MATHEMATICS LEARNING OUTCOMES THROUGH QUANTUM TEACHING METHOD - Andi Mariani Ramlan (JME (Journal of Mathematics Education), 2017)
As educators must be professional in choosing strategies, learning methods and techniques in directing competent students, especially learning mathematics. Maximizing learning activities as one of the efforts of educators by using one of the learning methods as a tool to achieve the planned learning objectives, so that all the potentials of students in the end can optimize the results of learning mathematics. The formulation of the problem in this research is "Whether by using the method of learning Quantum Teaching on trigonometric basic competence can improve students' learning outcomes of grade X.3 SMA Negeri 1 Wundulako?" The procedures of this research are planning, action implementation, observation and evaluation, and reflection. Sources of data in this study are teachers of mathematics (teacher partners), observers and students. Type of data collected is quantitative data, in the form of student learning outcomes and qualitative data, namely the observation of teachers as researchers and students. Data collected, analyzed by using quantitative and qualitative analysis. The results showed that: (1) the average score of the students' mathematics learning outcomes in the first cycle was 60.13 with the standard deviation of 13.58 and was in the medium category. In cycle II obtained the average value of learning outcomes mathematics of 78.18 with standard deviation of 10.99 is in the high category; (2) the total number of students who completed the study 60.53% ie 23 of 38 students in the first cycle, to 94.74% or 36 of 38 students in cycle II and categorically completed classically; (3) Quantum Teaching learning method can also increase the spirit, motivation to succeed and enthusiasm of student at the time of learning, based on observation result of researcher, partner teacher and observer. From the results of this study can be concluded that with the implementation of learning methods Quantum Teaching on trigonometric basic competence can improve students' learning outcomes of grade X.3 SMA Negeri 1 Wundulako.